Pengaruh Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Matematika Kelas V Materi Kelipatan dan Faktor di SD Negeri 04 Sungai Rumbai - Hader, Antik Estika; Darniyanti, Yulia; Wirdana, Wira Ayu Kusuma (Jurnal Ilmiah Dikdaya, 2024)
The aim of the research that will be carried out is to determine the effect of the differentiated learningmodel on the mathematics learning outcomes of class V students at SD Negeri 04 Sungai Rumbai. This researchis experimental research that uses a pre-experimental research design, with a two group pretest design. Theresearch sample consisted of 34 students who were all class V students, consisting of 2 classes, namely VA andVB, each class numbering 17 students. The data collection instrument used was a 25-item multiple choice test,which had been tested for validity and reliability. The results of this research show that the averagemathematics learning outcome of students in the experimental group with differentiated learning is 76 and forthe control class with conventional learning is 56.4, so it is in accordance with the testing criteria of reject ?0and accept ?1. so that the average mathematics learning outcomes of students who are taught using thedifferentiated learning model are better than the mathematics learning outcomes of students who useconventional learning. Thus, it can be concluded that there is a significant influence from the application of thedifferentiated learning model on the learning outcomes of students in mathematics in multiples and factors inclass V at SD Negeri 04 Sungai Rumbai